PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS ECOPRENEURSHIP DAN KREATIVITAS PADA PEMBELAJARAN IPAS TERHADAP LITERASI LINGKUNGAN - Dewi Wulan Angraeni; Imam Farisi, Mohammad; Suhartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the ecopreneurship-based Project Based Learning (PjBL) model and students’ creativity on environmental literacy in IPAS (Science and Social Studies) learning among fifth-grade students at SDN Candrajaya I. Using a quantitative approach with a quasi-experimental design, the research involved 41 students divided into two groups: an experimental class applying the ecopreneurship-based PjBL model and a control class using the Problem Based Learning (PBL) model. Data were analyzed using multiple linear regression. The results showed that the ecopreneurship-based PjBL model had a significant effect on improving students’ environmental literacy (significance value 0.024 < 0.05), while students’ creativity did not show a significant effect (significance value 0.798 > 0.05). Simultaneously, both independent variables did not have a significant influence on environmental literacy (significance value 0.070 > 0.05).